Presenting for Duty: Lessons From A Specialty Surgery Division at the Pandemic Epicenter. Issue 2 (15th December 2020) - Rao, Roshni; Sun, Luona; Acevedo, Charise; Concepcion, Ana; Concepcion, Dionisia; Sanchez, Josenny; Alicea, Catherine; Franco, Lisa; Frias, Rosanna; Flores, Adrianna; Vega, Armisia; Baez, Jennifer; et al.
Abstract : Mini-abstract: The coronavirus disease 2019 (COVID-19) pandemic has had catastrophic repercussions across the world and here in the United States. The healthcare system in New York City, the epicenter, has faced significant disruptions due to the sheer volume of cases and critical care needs of severely ill patients. For surgical specialty services, the postponement of all elective surgeries, redeployment of faculty and staff, and cancellation of outpatient clinics became a rapid reality. These circumstances required a nimble restructuring of services and communications to facilitate continued support of academic and clinical missions. Throughout the course of the pandemic, significant adjustments were made in regards to duties, patient services, and communication. The frameworks and techniques utilized are described along with the relevant outcomes. Immediate restructuring of tumor boards, a focused multidisciplinary approach to management that incorporated the barriers presented by the pandemic, optimization of telehealth services, inclusive communication, and a service-oriented approach to redeployment were critical to sustaining the Division of Breast, Melanoma, and Soft Tissue surgery.